Compositional Fluctuations Locked by Athermal Transformation Yielding High Thermoelectric Performance in GeTe. Issue 1 (20th November 2020) - Tsai, Yi‐Fen; Wei, Pai‐Chun; Chang, Liuwen; Wang, Kuang‐Kuo; Yang, Chun‐Chuen; Lai, Yen‐Chung; Hsing, Cheng‐Rong; Wei, Ching‐Ming; He, Jian; Snyder, G. Jeffrey; Wu, Hsin‐Jay
Abstract: Phase transition in thermoelectric (TE) material is a double‐edged sword—it is undesired for device operation in applications, but the fluctuations near an electronic instability are favorable. Here, Sb doping is used to elicit a spontaneous composition fluctuation showing uphill diffusion in GeTe that is otherwise suspended by diffusionless athermal cubic‐to‐rhombohedral phase transition at around 700 K. The interplay between these two phase transitions yields exquisite composition fluctuations and a coexistence of cubic and rhombohedral phases in favor of exceptional figures‐of‐merit zT . Specifically, alloying GeTe by Sb2 Te3 significantly suppresses the thermal conductivity while retaining eligible carrier concentration over a wide composition range, resulting in high zT values of >2.6. These results not only attest to the efficacy of using phase transition in manipulating the microstructures of GeTe‐based materials but also open up a new thermodynamic route to develop higher performance TE materials in general. Abstract : The interplay between phase decomposition and athermal phase transition is leveraged in a Ge–Sb–Te ternary system to enable exquisite microstructure features by strong composition fluctuations and coexistence of rhombohedral and cubic GeTe. Specifically, alloying GeTe with Sb2 Te3 significantly suppresses thermal conductivity while retaining eligible carrier concentration over a wide composition range, resulting in high zT values of >2.6.